2020
DOI: 10.1097/sla.0000000000004464
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Perineural Invasion on Disease Recurrence and Survival After Pancreatectomy for Pancreatic Head Ductal Adenocarcinoma

Abstract: Objective: To describe PNI and to evaluate its impact on disease-free (DFS) and overall survival (OS) in patients with resected pancreatic ductal adenocarcinoma (PDAC). Summary of Background Data: Although PNI is a prognostic factor for survival in many GI cancers, there is limited knowledge regarding its impact on tumor recurrence, especially in ''early stage disease'' (PDAC ≤20 mm, R0/ N0 PDAC). Methods: This multicenter retrospective study included patients undergoing PDAC resection between 2009 and 2014. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 28 publications
5
42
1
1
Order By: Relevance
“…A number of retrospective studies have shown that the postoperative survival rate of PDAC patients was negatively correlated with nerve infiltration [ 10 , 98 101 ] (Table 3 ). One recent multicenter retrospective study enrolling 778 PDAC patients who received surgical treatment between 2009 and 2014 showed that the rate of PNI was 87% among these patients (T0/1, 61.6%; T2, 86.7%; T3/4, 90.1%; N0, 72.5%; and N1, 93.0%) [ 102 ]. PNI was an independent risk factor for disease‐free survival (DFS) and/or OS ( P < 0.0001) [ 103 ], and could serve as a prognostic indicator [ 99 , 104 , 105 ].…”
Section: Clinical Significance Of Pnimentioning
confidence: 99%
“…A number of retrospective studies have shown that the postoperative survival rate of PDAC patients was negatively correlated with nerve infiltration [ 10 , 98 101 ] (Table 3 ). One recent multicenter retrospective study enrolling 778 PDAC patients who received surgical treatment between 2009 and 2014 showed that the rate of PNI was 87% among these patients (T0/1, 61.6%; T2, 86.7%; T3/4, 90.1%; N0, 72.5%; and N1, 93.0%) [ 102 ]. PNI was an independent risk factor for disease‐free survival (DFS) and/or OS ( P < 0.0001) [ 103 ], and could serve as a prognostic indicator [ 99 , 104 , 105 ].…”
Section: Clinical Significance Of Pnimentioning
confidence: 99%
“…Albumin concentration and lymphocyte count, which are the common indicators of nutritional status, are important predictors of nutritional risk and postoperative complications. PNI, which is calculated using serum albumin concentration and absolute lymphocyte count, is considered an essential predictive indicator of different types of human cancers [24,25,26]. As a hallmark of cancer that fosters recurrence, progression and metastasis, tumour-associated systemic in ammation has been extensively reviewed in recent years [27].…”
Section: Discussionmentioning
confidence: 99%
“…Using a more accurate matching process, based on a previously described nomogram for resected pancreatic cancer [57], Yopp et al [42] found a significantly superior survival in IPMC (the 5-year OS of 68% versus 23% in cPDAC). However, this study did not include vascular invasion and perineural invasion, which are two main accepted prognostic factors for resected cPDAC [58,59], in matching parameters. Contrarily, in the study by Duconseil et al [60], patients were matched by perineural invasion, tumor stage, lymph node ratio, and margin status and no statistical differences in survival were observed.…”
Section: Pathological Features and Survival Of Ipmcs 41 Ipmc Versus Cpdacmentioning
confidence: 99%